Analisis Faktor Penyebab Rendahnya Motivasi Belajar IPS Pada Pembelajaran Tatap Muka Pasca Pandemi - Retno Kuning Dewi Pusparatri; iah Nadiatul Jannah; Primajati Endarwanto; Jekcson Wuwute; Edison Edison; Pinta Hayu Faizzana; Supardi Supardi (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The purpose of this study was to describe the factors causing low social studies motivation in face-to-face learning after the pandemic (Covid-19) at SMA Negeri 1 Seyegan. This study uses a type of qualitative research conducted at SMA Negeri 1 Seyegan Sleman Yogyakarta. The subjects of this study were the Subject Teachers of Social Science Subjects and Students at SMA Negeri 1 Seyegan. Data were analyzed using data reduction, data presentation, and drawing conclusions. The results of the study show that after online learning has been carried out for approximately 1.5 years, it has a significant influence on students' learning motivation. Face-to-face learning was carried out starting at the end of 2021 and the results obtained were that the factors causing the low learning motivation of students were that the learning motivation of students had decreased because they were still adapting to face-to-face learning, they still had a tendency to depend on smartphones to find answers to the assignments given, the absence of the National Examination as a determinant of graduation, as well as the learning process which is monotonous and pays little attention to the aspirations of students. Efforts that can be made by schools to increase learning motivation are of course teachers can choose learning models that are more creative and innovative so that the learning atmosphere becomes more enjoyable. Through the right learning model will have a positive impact on the development of students' learning motivation.